Cholera Toxin Production in Vibrio cholerae O1 El Tor Biotype Strains in Single-Phase Culture - Baek, Yeongjun; Lee, Donghyun; Lee, Jiwon; Yoon, Youngbae; Nair, G. Balakrish; Kim, Dong Wook; Kim, Eun Jin (Frontiers in Microbiology, 2020)
Vibrio cholerae O1 serogroup strains have been classified into classical and El Tor biotypes. Cholera, a life-threatening diarrheal disease, can be caused by either biotype through the cholera toxin (CT) that they produce. To increase our knowledge of the pathogenicity of bacteria, we must understand the toxigenicity of bacteria. CT production by classical biotype strains in simple single-phase cell cultures has been established; however, special culture media and growth conditions that are not appropriate for mass production of CT are required to facilitate CT production in El Tor biotype strains. In this report, we produced CT in El Tor biotype strains using simple media and single-phase culture conditions. A single point mutation in ToxT, a transcriptional activator of Toxin Co-regulated Pilus (TCP) and cholera toxin, enabled the El Tor biotype strains to produce cholera toxin in similar quantities as classical biotype strains in single-phase laboratory culture conditions. CT production capacity varied between El Tor biotype strains. Wave 2 and 3 atypical El Tor strains tended to produce more CT than prototype Wave 1 strains. Wave 2 and 3 strains lack neutral fermentation; however, the capacity for neutral fermentation was not associated with significant differences in CT production by El Tor biotype strains. The Wave 3 strain that caused the 2010 cholera outbreak in Haiti produced CT only when neutral fermentation was abolished. The disparity in CT production between the seventh cholera pandemic strains highlight the differences in virulence between strains and the cause of population changes in V. cholerae.